A Case Study on the Non-price Factors and Consumer Behaviour for Pangasius (Pangasianodon hypophthalmus) (Valenciennes, 1840) Consumption in Pune City, India - Mugaonkar, P.; Kumar, N. R.; Shelar, Gauri; Polanco, J. F.; Ramsubramanian, V.; Biradar, R. S. (Fishery Technology, 2017)
The consumption and preferences of Pangasius and the constraints in the same have been investigated among consumers in Pune city, Maharashtra, India. Though 85.83% of respondents were aware about the Pangasius as new catfish available for consumption, only 38.33% of them consumed it. Consumers quoted â€˜oilinessâ€™ (high fat content) of Pangasius as the prime reason for non-consumption. Only 37.5% of consumers were willing to try processed Pangasius. The consumers of â€œlow incomeâ€ and â€œhigh incomeâ€ group showed significant difference in their expenditure on Pangasius. â€œLow incomeâ€ group consumers spent more on Pangasius compared to â€œHigh incomeâ€ group. Consumption of Pangasius can be improved by improving its quality and creating awareness on perceived health hazards. Different cooking methods or use of Pangasius as raw material for other products may solve the problem of â€˜oilinessâ€™ and may become popular among high income group consumers.